Sexual education for adolescents: parent role in rural area - Ema Waliyanti; Ratna Ajeng Dewantari (Journal of Health Technology Assessment in Midwifery, 2021)
Health problems faced by adolescents when they are very varied and related to risky sexual behavior. Sexual education is currently still considered taboo by the public because it is less appropriate to talk about and is private. The purpose of this study was to explore the role of parents in sexual education in adolescents. This study uses a qualitative research method with a phenomenological approach. Data were collected by means of in-depth interviews with 12 participants who were determined by purposive sampling. The saturation data with 5 parent and 7 adolescents. Data validity test used source triangulation, member cheking, peer debrifing, and thick description. Data analysis using open code 4.03 software. This research is ethical with number No. 020 / EC-KEPK FKIK UMY / I / 2021.  The results showed that the role of parents in providing sex education to adolescents was caused by several factors, namely the closeness of children to their parents, parental education, parental divorce, parents' perceptions of sex education, perceptions of the importance of sex education, and parenting styles of parents to child, which affect the optimal role of parents in sex education for their children. To conclude, it is important for parents to provide sexual education to prevent risky sexual behavior, such as providing sexual education for adolescents, giving advice to children, supervising children's relationships, and providing rules for children.